Education Innovation: Religious-Based Local Content Curriculum in Solok Regency - Yafi, Salman; Kosim, Muhammad (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
The development of times marked by an increase in globalization impacts the morals and ethics of the nation's next generation. Innovation is therefore necessary to prevent moral erosion and foster religious character formation. This study aims to explain educational innovation in the form of a religious-based local content curriculum in terms of (1) purpose; (2) material; (3) media; (4) approach; and (5) evaluation. We employed qualitative methods in this investigation. The research findings indicate that the Solok District Government has innovated in education by developing a Religious-Based Local Content Curriculum policy to foster a religious character at the formal education level. The goal is to help students understand the region's spiritual values and local wisdom. The curriculum comprises stand-alone subjects and integrated study materials with relevant subjects. The learning module includes printed and written media. The learning module lays out the learning strategy. The evaluation is formative, summative, and authentic. This study serves as a reference for developing religion-based local content curricula.